Changes in returns to education for off-farm wage employment: evidence from rural China. Issue 1 (27th July 2018) - Wang, Weidong; Dong, Yongqing; Luo, Renfu; Bai, Yunli; Zhang, Linxiu
Abstract : Purpose: The purpose of this paper is to examine the role of education in the labor market and to understand how returns to education change over time in rural China. Design/methodology/approach: Using nationally representative survey data from 2004 to 2015, this study provides insights on wage determination in the labor market and examines how the returns to education in rural China differ with time and educational endowment. This study applies ordinary least squares estimation and the Heckman selection model to estimate the returns to education. Findings: The returns to education decreased during the observed years from more than 6 percent in 2004 to only about 3 percent in 2011, rising to nearly 4 percent in 2015. The overall trend is robust and observed within groups defined by education. Additionally, the returns to education vary greatly with educational endowment. Tertiary education has always maintained a high rate of returns at nearly 10 percent, while returns to senior high school education and below have gradually diminished. Originality/value: The authors believe that the results will not only enrich studies on the returns to education in rural China, but also provide a basis for diagnosing the changes of rural labor market in the early twenty-first century.